2004
DOI: 10.1002/polb.20056
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline‐solution‐induced crystallization in poly(butylene terephthalate)

Abstract: Subtle crystalline structure changes of poly(butylene terephthalate) (PBT) specimens treated with an alkali solution at room temperature were investigated with the grazing incidence X‐ray diffraction (GIXRD) analysis method. A new phenomenon was found: the aqueous alkali solution induced the crystallization of the PBT polymer. Under the GIXRD analysis condition of an incidence angle of 1°, the penetration depth of the X‐ray in PBT was less than 80 μm, and this agreed well with the rough theoretical estimation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The THF apparently acts like a nucleating agent, providing heterogeneous nucleation sites for the crystallization of the pCBT as well as increased chain mobility. Moreover, polyesters are known to undergo chemical‐induced crystallization 25–30. Therefore this increase in crystallinity is likely to be due to a solvent‐induced crystallization phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…The THF apparently acts like a nucleating agent, providing heterogeneous nucleation sites for the crystallization of the pCBT as well as increased chain mobility. Moreover, polyesters are known to undergo chemical‐induced crystallization 25–30. Therefore this increase in crystallinity is likely to be due to a solvent‐induced crystallization phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…Having polyester products brought into contact with liquid amines has to allow for the interaction of solvents on the increase of free volume and subsequent lowering glass‐transition temperature, its plasticizing effects, and inducing crystallization. The process of solvent‐induced crystallization of polyesters has been studied since 1949 43–56 . At first, it was found that several liquids initiate crystallization of PET at room temperature, well below the glass transition temperature 43 .…”
Section: General Aspectsmentioning
confidence: 99%
“…By exposure of PLA to 50% and 95% ethanol solutions α‐form crystals was detected 54 . Grazing incidence X‐ray diffraction analysis shows at room temperature an aqueous sodium hydroxide solution (2.5 N) induces crystallization on the surface layers of PBT polymer film 55 …”
Section: General Aspectsmentioning
confidence: 99%
See 2 more Smart Citations